Aspectos analíticos em TS-FF-AAS: estudo de interferências e aplicação para a determinação de metais em vinhos e sucos - Schiavo, Daniela (Universidade Federal de São Carlos, 2007)
In this work, it was evaluated the effects of interferences caused by major and minor constituents on Co, Cu and Mn atomized by flame atomic absorption spectrometry (FAAS) and by thermospray flame furnace atomic absorption spectrometry (TS-FFAAS). The main concomitants were chosen according to the typical concentrations found in foods and beverages. The liquid samples were propelled by a peristaltic pump through a ceramic capillary conductively heated by a flame and then into a nickel tube. The nickel tube was positioned on a lab-made stainless steel support with four ceramic pins on the flame burner. The thermospray was generated inside the heated ceramic capillary in contact with the nickel tube. The samples were introduced into the flame heated tube without the need of a nebulizer. Additionally, the sensitivity was significantly improved by increasing the residence time of the free analyte atoms in the observation zone. Severe interference effects were observed for all analytes. These interference processes require the application of either previous separation steps or special strategies of calibration. Afterwards, the applicability of TS-FF-AAS was evaluated for direct determination of Cu, Cd and Pb in wines and grape juices. The developed procedure did not require any step of digestion. The effect of ethanol was evaluated and samples were properly diluted before measurements. All determinations were carried out adopting optimized conditions and quantification was based on the standard additions method. Limits of detection (LOD) of 12.9, 1.7 and 5.32 µg L-1 (n = 14) for Cu, Cd and Pb, respectively, were obtained using optimized conditions for wine samples. Relative standard deviations (RSD, %) of 2.7, 2.1 and 2.6% for Cu, Cd and Pb were obtained (n = 6). Limits of detection (LOD) for grape juice samples were 13.7, 0.90 and 5.55 µg L-1 and relative standard deviations (RSD, %) of 3.3, 2.0 and 2.3 for Cu, Cd and Pb, respectively. The analytical throughput was 45 determinations h-1 and accuracy was proved by addition-recovery experiments.
Analytical aspects of ts-ff-aas: study of interferences and application for determinations of metals in wines and grape juices
Keywords: Espectroscopia de absorção atômica; TS-FF-AAS; Forno sobre chama; Interferência; Vinho; Suco; CIENCIAS EXATAS E DA TERRA::QUIMICA